2019
DOI: 10.1007/s12298-018-0633-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of chitosan on plant responses with special reference to abiotic stress

Abstract: Chitosan is a natural biopolymer modified from chitins which act as a potential biostimulant and elicitor in agriculture. It is non-toxic, biodegradable and biocompatible which favors potentially broad application. It enhances the physiological response and mitigates the adverse effect of abiotic stresses through stress transduction pathway via secondary messenger(s). Chitosan treatment stimulates photosynthetic rate, stomatal closure through ABA synthesis; enhances antioxidant enzymes via nitric oxide and hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
145
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(161 citation statements)
references
References 118 publications
9
145
0
7
Order By: Relevance
“…The potential of chitosan application has been studied in many horticultural crops, towards inducement of defense mechanisms, improved agronomic traits, easier post-harvest management of fruits and vegetables, augmented plant growth and physiological activities, including as a bio-fertilizer/fertilizer protectant [5], and enhanced abiotic stress management properties [6]. Some reports demonstrated its potential effect on powdery mildew [7] and gray mold control [8] in grapevine.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of chitosan application has been studied in many horticultural crops, towards inducement of defense mechanisms, improved agronomic traits, easier post-harvest management of fruits and vegetables, augmented plant growth and physiological activities, including as a bio-fertilizer/fertilizer protectant [5], and enhanced abiotic stress management properties [6]. Some reports demonstrated its potential effect on powdery mildew [7] and gray mold control [8] in grapevine.…”
Section: Introductionmentioning
confidence: 99%
“…El Amerany et al [24] found similar result in tomato plant grown in soil amended with chitosan and compost. The positive effects of Ch on tomato growth and flowering might be due to its properties to act as anti-transpirant, to activate ROS scavenging system, to enhance stomatal conductance, and to stimulate growth of xylem vessels [24,36]. Moreover, application of Ch to leaves is known to increase the rate of photosynthesis leading to improved growth and overall plant development [37].…”
Section: Discussionmentioning
confidence: 99%
“…This protein is homologous of chitinase V in Arabidopsis which has a significant role in salt stress in addition to defense against pathogenic attack [43], and loss of function of the gene encoding chitinase-like protein results in overaccumulation of Na + in the cytosol [44]. In stomata, it has been reported that chitosan, which can be produced by chitinase, mediates stomatal narrowing and it may be advantageous for both the salt stress responses and plant defense [45,46].…”
Section: Stress Related Proteins Differentially Abundant Proteins In mentioning
confidence: 99%